Family Spongiidae Gray, 1867. Pp. 1051-1060. In: Hooper, J.N.A. & Van Soest, R.W.M. (eds) Systema Porifera - A guide to the classification of sponges. (2 volumes) Kluwer Academic/ Plenum Publishers, New York, 1708 + xvliii. - Cook, S. de C.; Bergquist, P.R. (2002)
Spongiidae Gray (Demospongiae, Dictyoceratida) consists of six valid genera, one of which, Spongia, includes three subgenera. There are 91 nominal species. Spongiids are characterised by their homogeneous skeletal fibres and dense fibre skeleton. Within the family, the most important characters used to distinguish genera are surface armouring, skeletal morphology, and the development of sub-dermal or internal lacunae. Choanocyte chambers are diplodal, and the amount of collagen reinforcing within the matrix is variable.